2016
DOI: 10.1016/j.ijthermalsci.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Novel design of delta winglet pair vortex generator for heat transfer enhancement

Abstract: Heat transfer is a naturally occurring phenomenon that can be greatly enhanced with the aid of vortex generators (VG). Three-dimensional numerical simulations of longitudinal vortex generators are performed to analyze heat transfer enhancement in parallel plate-fin heat exchanger. The shear-stress transport (SST) k-u model is adopted to model the flow turbulence. Empirical correlations from the open literature are used to validate empty channel simulations. First, numerical simulations are conducted for the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Their results indicated that WVGs could generate longitudinal and transverse vortices to induce both impingement flow and recirculation zone leading to higher heat transfer and comparatively lower pressure drop. Based on decreasing pressure drop, an innovative vortex generator configuration, named inclined projected winglet pair was examined by Oneissi et al Their design showed superior performance relative to the classical delta winglet pair.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that WVGs could generate longitudinal and transverse vortices to induce both impingement flow and recirculation zone leading to higher heat transfer and comparatively lower pressure drop. Based on decreasing pressure drop, an innovative vortex generator configuration, named inclined projected winglet pair was examined by Oneissi et al Their design showed superior performance relative to the classical delta winglet pair.…”
Section: Introductionmentioning
confidence: 99%
“…The performance ratio, (Nua/Nuc), based on equal pumping power and constant heat transfer area, has found to be in the range of 1.0 to 6.0. M. Oneissi et al [14] checked novel design of delta winglet pair vortex generator for heat transfer enhancement. numerical simulations are conducted for the classical delta winglet pair (DWP) which is introduced as the reference case in there study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…FLUENT has well-validated physical modelling capable of delivering fast, accurate results for multiphysics applications, and has been widely applied in numerical simulation and is considered to be a very powerful CFD tool. As shown in Table 2, most of the published CFD works in the past ten years have applied FLUENT software, for example, References [4,16,48,[77][78][79][80][82][83][84][85][86][87][89][90][91][92][93]95,96,100,103,[105][106][107].…”
Section: -9700mentioning
confidence: 99%